The Impact of Kinesthetic and Gamification Based KUBITA SIPA Learning Media on Water Cycle Learning Outcomes among Fifth Grade Students at Muhammadiyah 4 Elementary School, Surabaya - Tsabita Salsabila; Holy Ichd Wahyuni; Fajar Setiawan (The Future of Education Journal, 2026)
Science learning on the topic of the water cycle in elementary schools often presents challenges due to its abstract nature and the extensive use of scientific terminology. This study aims to examine the effect of KUBITA-SIPA (Interactive Science Cube), a kinesthetic and gamification-based learning media, on students' learning outcomes. The study employed a quantitative approach using a one-group pretest-posttest pre-experimental design. The participants consisted of 24 fifth-grade students from Class V-C at Muhammadiyah 4 Elementary School, Surabaya. Data were collected using pretests and posttests, while data analysis was conducted through descriptive statistics, a normality test, and hypothesis testing using a paired-samples t-test. The results showed that the mean pretest score of 58.33 increased to 81.25 on the posttest. The hypothesis test yielded a significance value of < 0.001 (< 0.05), indicating a statistically significant difference between students' learning outcomes before and after the intervention. Therefore, it can be concluded that the KUBITA-SIPA learning media has a significant positive effect on improving students' understanding of the water cycle concept.